Decoction, infusion and hydroalcoholic extract of cultivated thyme : antioxidant and antibacterial activities, and phenolic characterisation - Martins, Natália (2015)
Bioactivity of thyme has been described, but mostly related to its essential oils, while studies with aqueous extracts are scarce. Herein, the antioxidant and antibacterial properties of decoction, infusion and hydroalcoholic extract, as also their phenolic compounds, were evaluated and compared. Decoction showed the highest concentration of phenolic compounds (either phenolic acids or flavonoids), followed by infusion and hydroalcoholic extract. In general, the samples were effective against gram-positive (Staphylococcus aureus and Staphylococcus epidermidis) and gram-negative (Escherichia coli, Klebsiella spp., Pseudomonas aeruginosa, Enterococcus aerogenes, Proteus vulgaris and Enterobacter sakazakii) bacteria, with decoction presenting the most pronounced effect. This sample also displayed the highest radical scavenging activity and reducing power. Data obtained support the idea that compounds with strong antioxidant and antibacterial activities are also water-soluble. Furthermore, the use of thyme infusion and decoction, by both internal and external use, at recommended doses, is safe and no adverse reactions have been described.